PHARMACEUTICAL CHEMISTRY AND COVID-19: DEVELOPMENT OF THERAPEUTICS AND PREVENTIVE DRUGS - Ventura, Camilla (LUMEN ET VIRTUS, 2023)
The global outbreak of COVID-19 has underscored the critical importance of pharmaceutical chemistry in addressing emerging public health threats. This article explores the multifaceted role of pharmaceutical chemistry in the development of antiviral drugs, vaccine delivery systems, monoclonal antibodies, and supportive therapies for the treatment and prevention of SARS-CoV-2 infection. Through detailed analysis of compounds such as remdesivir, molnupiravir, and nirmatrelvir, and the use of advanced technologies including lipid nanoparticles and structure-based drug design, the paper highlights the speed and precision with which pharmaceutical chemists responded to the pandemic. It also examines the dynamic adaptation to viral mutations and resistance mechanisms. The findings demonstrate how interdisciplinary collaboration, molecular innovation, and real-time chemical strategies were essential in saving lives and preparing for future health emergencies.